Inferno - Brown, Dan, 1964- (London : Bantam Press, 2013)
Dan Brown's new novel, Inferno, features renowned Harvard symbologist Robert Langdon and is set in the heart of Europe, where Langdon is drawn into a harrowing world centred around one of history's most enduring and mysterious literary masterpieces. As Dan Brown comments: 'Although I studied Dante's Inferno as a student, it wasn't until recently, while researching in Florence, that I came to appreciate the enduring influence of Dante's work on the modern world. With this new novel, I am excited to take readers on a journey deep into this mysterious realm' a landscape of codes, symbols, and more than a few secret passageways.
Keywords: Dante Alighieri, -- 1265-1321 -- Fiction; Langdon, Robert -- (Fictitious character) -- Fiction; Cryptographers -- Fiction; Florence (Italy)